Peran Religiusitas Dalam Proses Penyembuhan Penderita Gangguan Kecemasan Umum Atau Generalized Anxiety Disorder (Gad) - Evi Radja Gae; Martina Novalina; Alvin Koswanto (Vox Dei: Jurnal Teologi dan Pastoral, 2023)
ABSTRACT The goal of this study is to ascertain how religion affects recovery from generalized anxiety disorder (GAD). The research's context is an example of a teacher's worry at a Christian school in Kupang Regency, which led to the teacher's subpar performance. The researcher's method of inquiry was qualitative. The author employed a literature review and open-ended interviews as data-gathering methods. The research informant worked as a teacher in Kupang Regency, East Nusa Tenggara, at a private Christian school. The findings of this study suggest that religion can help people with generalized anxiety disorder (GAD) feel less anxious. Religiosity can lessen anxiety in people with generalized anxiety disorder (GAD), yet it cannot totally heal the condition.